Anesthesia in pregnant women with HELLP syndrome: case report - Zuccolotto,Eduardo Barbin (2016)
Abstract Background and objectives: HELLP syndrome, characterized by hemolysis, high levels of liver enzyme, and low platelet count, is an advanced clinical stage of pre-eclampsia, progressing to high maternal (24%) and perinatal (up 40%) mortality, despite childbirth care in a timely manner. The goal is to describe the anesthetic management of a case with indication to emergency cesarean. Case report: Female patient, 36 years old, gestational age of 24 weeks, with hypertensive crisis (BP 180/100 mmHg) and severe headache, was admitted to the operating room for a cesarean section after diagnosis of HELLP syndrome. Indicated for general anesthesia, we opted for total intravenous with intubation after rapid sequence induction with propofol and remifentanil in continuous target-controlled infusion, and rocuronium at a dose of 1.2 mg/kg. Maintenance was achieved with propofol and remifentanil. The surgical procedure was uneventful, the child was born with APGAR 1/5 and transferred to the NICU. At the end of surgery, the patient was extubated in the operating room and taken to the ICU. The postoperative period was uneventful with no changes worthy of note and the patient was discharged on the sixth postoperative day. Conclusion: When general anesthesia is the choice in parturient with HELLP syndrome, tracheal intubation with rapid sequence induction due to possible difficult airway, as well as the use of drugs to control the hemodynamic response can minimize the complications associated with the procedure, as occurred in this case.